Human platelet gel supernatant inactivates opportunistic wound pathogens on skin. (February 2015) - Edelblute, Chelsea M.; Donate, Amy L.; Hargrave, Barbara Y.; Heller, Loree C.
Abstract Activation of human platelets produces a gel-like substance referred to as platelet rich plasma or platelet gel. Platelet gel is used clinically to promote wound healing; it also exhibits antimicrobial properties that may aid in the healing of infected wounds. The purpose of this study was to quantify the efficacy of human platelet gel against the opportunistic bacterial wound pathogens Acinetobacter baumannii, Pseudomonas aeruginosa, and Staphylococcus aureus on skin. These opportunistic pathogens may exhibit extensive antibiotic resistance, necessitating the development of alternative treatment options. The antimicrobial efficacy of platelet gel supernatants was quantified using an in vitro broth dilution assay, an ex vivo inoculated skin assay, and in an in vivo skin decontamination assay. Human platelet gel supernatants were highly bactericidal against A. baumannii and moderately but significantly bactericidal against S. aureus in vitro and in the ex vivo skin model. P. aeruginosa was not inactivated in vitro; a low but significant inactivation level was observed ex vivo. These supernatants were quite effective at inactivating a model organism on skin in vivo. These results suggest application of platelet gel has potential clinical applicability, not only in the acceleration of wound healing, but also against relevant bacteria causing wound infections.